Mediation through art: from listening in process to relational form - Pimenta, Bruno Bissoli (Guará Journal, 2025)
This visual essay documents the creative process behind two mural interventions carried out as field research: Caminhos da Segurança (2024), at the Community Information and Assistance Post in Itabira (MG, Brazil), and Gerações dos Vales Mineiros (2025), at the Socio-Informative Centre for Tailings Dam Decommissioning of the Mariana Complex in Ouro Preto (MG, Brazil). Both murals form part of the mediation trail designed to disseminate information about safety measures for dam areas, and they constitute the first exhibition space of these centres, where listening takes place after the mediation of the narrative. The transdisciplinary method of collaborative creation articulates concepts drawn from circle processes with nonviolent communication and the culture of peace. Within the field of art, it draws on the notions of social sculpture and relational aesthetics in order to act structurally upon the connection of relations and the formation of human bonds during the social interstice of the artistic process. The experience shows how the communicative capacity of mural art manifests itself in diverse forms and how the image projected onto space mediates a narrative that engages audiences and relates them to a given time.
Keywords: Muralism; Sociocultural mediation; Relational aesthetics; Circle processes; Site-specific art